PHYTOCHEMICAL SCREENING AND ANTIBACTERIAL PROPERTIES OF Punica granatum EXTRACTS AGAINST GASTROINTESTINAL INFECTION AN In-vitro STUDY - VAKAYIL, RAMSI; KABEERDASS, NIVEDHITHA; KUPPUSAMY, ABIRAMI; MATHANMOHUN, MAGHIMAA (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2019)
Background: Punica granatum Linn is a bearing fruit shrub, belonging to the family Lythraceae. Every part of this plant is useful for humans such as seeds and fibers endow with vitamins-C, K and folate. Oil acids of punica, palmitic, stearic and oleic acid present in the seeds. Pomegranate is generally used as a conventional medication in India for the cure of enteric bacterial pathogens. Aim: To study the phytochemicals and antibacterial activities of aqueous, alcoholic and chloroform crude extracts of P. granatum peel against some enteric pathogens. Materials and Methods: The isolates were examined by Foldscope microscopy and biochemical tests. Phyto-chemical study analyzed the existence of alkaloids, flavonoids, phenols, saponins, terpenoids, steroids, tannins, reducing sugars, carbohydrates, and amino acids. Vancomycin, tetracycline, chloramphenicol, gentamycin, and co-trimoxazole are the antibiotic disc used in the disc diffusion assay. Results: A multidrug-resistant pattern was observed in the isolated pathogens. As reported by natural medicine P. granatum is used for the treatment of enteric pathogens. Antimicrobial activity was performed by the standard procedure (Kirby-Bauer’s – agar well diffusion method) using pomegranate extracts (aqueous, alcoholic and chloroform) against the enteric pathogens. Peel crude extracts of P. granatum were showed various degrees of antibacterial activities with the maximum mean inhibition zones reaches 36±1.0 mm in diameter for methicillin-resistant Staphylococcus aureus (MRSA) with ethanolic extract. The highest zone of clearance was found in ethanolic extract followed by aqueous extract, but only the lowest zone was in chloroform extract. Most significant inhibition was observed against Staphylococcus aureus, Vibrio cholerae, Pseudomonas aeruginosa, Proteus vulgaris, E. coli, Salmonella typhi, Shigella dysentriae followed by Klebsiella sp. Conclusion: The end result attained that the peel extracts of Punica granatum have impressive pharmaceutical bioactive compounds and antibacterial property. It is used as natural medicine by itself to treat gastrointestinal disorders.